Options for strengthening economic co-operation between Cuba and the other Latin American and Caribbean countries (SELA CaracasVE)
Focuses on Cuba and its economy. Examines bases for Cuban cooperation with the region and looks at three main ways in which Cuba's cooperation with the Latin American and Caribbean countries could be strengthened.
DC